POS0807 A TRANSCRIPTIONAL PROFILE OF FATIGUE IN PRECLINICAL AUTOIMMUNITY WHICH IS PRESERVED IN SLE AND SJOGREN'S SYNDROME - Carter, L.M.; MD Yusof, M.Y.; Plant, D.; Bauer, J.; Wenlock, S.; Alase, A.; Psarras, A.; Wigston, Z.; Vital, E. (Annals of the rheumatic diseases, 2023)
Fatigue is a prevalent and debilitating symptom in autoimmune connective tissue diseases (CTDs). Its immunological mechanisms are poorly understood. Although targeted therapies can improve fatigue, the effect is modest and variable. This is likely because, in established disease, immunological drivers of fatigue may be obscured by multifactorial effects from glucocorticoids, accrued damage and comorbidity. However, fatigue frequently pre-dates formal diagnosis or end-organ manifestations, suggesting immunological mechanisms may be better interrogated in the preclinical phase. SLE and primary Sjogren's syndrome (pSS) are preceded by a preclinical phase of anti-nuclear antibody (ANA) positivity with no or non-specific symptoms years before clinically manifest inflammation. Although only a minority ultimately develop overt CTDs, ANA-positive individuals demonstrate complex immune dysregulation including increased interferon (IFN) pathway activation [1]. We hypothesise that immune disturbances underlying fatigue in SLE and pSS are i) established during the earlier ANA-positive preclinical phase; ii) contribute to the symptom burden among ANA-positive individuals, and (iii) are differentially modulated in established disease states. To investigate unique and conserved peripheral blood immune cell transcriptional signatures associated with symptomatic fatigue in ANA-positive preclinical patients and established SLE and pSS. Bulk RNASeq was performed on peripheral blood mononuclear cells isolated from 35 ANA-positive preclinical individuals demonstrating ≤1 clinical criterion for classifiable CTD, symptom duration <12 months and naive of therapy, of whom 15 later progressed to SLE/pSS and 20 did not progress. Disease controls with SLE (n=18), pSS (n=10) were also analysed. Weighted gene co-expression network analysis was used to identify gene expression modules associated with fatigue in preclinical subjects. Consensus networks were constructed for Preclinical:SLE and Preclinical:pSS to identify fatigue-associated modular signatures which are retained in established CTDs. Gene ontology enrichment was evaluated using g:profiler. Within the preclinical transcriptomic network 5 module eigengenes showed significant and specific association with patient fatigue VAS. A type-I IFN signature, centred upon canonical ISGs, MX1, IRF7 and IFIT5, was positively correlated with fatigue score (R=0.48, p=0.003) and conserved across preclinical, SLE and pSS networks, with subtly different modular organisation. One further module, enriched for tRNA modification was significantly correlated with fatigue in preclinical subjects (R=0.41, p=0.01) but with no counterpart preserved in either SLE or pSS networks. The modular signature with strongest negative association with fatigue (R= -0.35, p=0.004) in preclinical subjects was enriched for mitogen-activated protein kinase (MAPK) cascades, heat shock and protein folding chaperone activity, and included transcription factors JUN and ATF3. This signature was retained in pSS patients, but did not persist in the SLE consensus network. We describe novel modular transcriptomic signatures associated with fatigue in the preclinical phase of autoimmunity which demonstrate differential persistence and activity in SLE and pSS. These pathways may help identify individuals with immune-mediated fatigue most amenable to therapy, and could provide insights into new therapeutic targets for fatigue across a range of autoimmune diseases. [1]Psarras et al. 2020 Nat Commun 11: 6149 NIL. Lucy Marie Carter Consultant of: UCB, Md Yuzaiful Md Yusof Consultant of: Aurinia Pharmaceuticals, UCB, Darren Plant: None declared, Julien Bauer: None declared, Stephanie Wenlock: None declared, Adewonuola Alase: None declared, Antonios Psarras: None declared, Zoe Wigston: None declared, Edward Vital Speakers bureau: AstraZeneca, Novartis, Paid instructor for: AstraZeneca, Novartis, Consultant of: UCB, Pfizer, Aurinia, Lilly, Roche, Genentech, Otsuka, GSK, Capella, Grant/research support from: Sandoz, AstraZeneca. [Display omitted]